Cytomegalovirus Infection Associated with Smaller Total Cortical Surface Area in Schizophrenia Spectrum Disorders. (7th April 2022) - Andreou, Dimitrios; Jørgensen, Kjetil Nordbø; Nerland, Stener; Yolken, Robert H; Haukvik, Unn K; Andreassen, Ole A; Agartz, Ingrid
Abstract: Objectives: Cytomegalovirus (CMV) congenital infection and in immunodeficiency can have deleterious effects on human cortex. In immunocompetent adults, the putative association between CMV infection and cortical measures has not been explored. We hypothesized that CMV exposure is associated with smaller cortical surface area or cortical thinning mainly in patients with schizophrenia spectrum disorders. Study Design: We included 67 adult patients with schizophrenia spectrum disorders and 262 adult healthy controls. We measured circulating CMV IgG antibody concentrations with solid-phase immunoassay techniques. We measured the total cortical surface area, regional cortical surface areas and the overall mean cortical thickness based on T1-weighted MRI scans processed in FreeSurfer v6.0. Study Results: In the whole sample analysis, we found a significant diagnostic group-by-CMV status interaction on the total surface area ( P = .020). Among patients, CMV antibody positivity was significantly associated with smaller total surface area ( P = .002, partial eta 2 = 0.138) whereas no such association was found in healthy controls ( P = .059). Post hoc analysis among patients showed that higher CMV antibody concentrations were also significantly associated with smaller total surface area ( P = .038), and that CMV antibody positivity was significantly inversely associated with 14 left and 16 right regional surface areas mainly in the frontal and temporal lobes. CMV infection was not associated with the overall mean cortical thickness. Conclusions: The results are indicative of a cortical surface area vulnerability to CMV infection in patients with schizophrenia spectrum disorders but not in healthy controls. CMV infection may contribute to the established cortical surface area aberrations in schizophrenia.